Breastfeeding and Its Protective Role Against Breast Cancer: A Meta-Analysis of Surgical and Non-Surgical Cases - Murti, Krina; Juliandra , Windy; Tua, Sampe (Journal of Society Medicine, 2025)
Introduction: Breast cancer is a leading cause of morbidity and mortality among women worldwide. Epidemiological studies have suggested that breastfeeding may reduce the risk of breast cancer, but evidence has been inconsistent. This meta-analysis aims to evaluate the association between breastfeeding and breast cancer risk, focusing on the effect of breastfeeding duration and menopausal status at the time of diagnosis. Methods: We conducted a systematic review of case-control and cohort studies published between 2020 and 2025 that assessed the relationship between breastfeeding and breast cancer risk. Studies were included if they provided data on breastfeeding history and its association with breast cancer risk, and if odds ratios (ORs) with 95% confidence intervals (CIs) were available or could be derived. Statistical analysis was performed using fixed and random-effect models to calculate pooled ORs, and subgroup analyses were conducted based on menopausal status and breastfeeding duration. Results: The meta-analysis included 10 studies with a total of 18,000 participants. The pooled OR for the association between ever breastfeeding and reduced breast cancer risk was 0.87 (95% CI: 0.80–0.94), indicating a modest reduction in risk. The protective effect was more pronounced in pre-menopausal women (OR = 0.75, 95% CI: 0.67–0.84), while the effect in post-menopausal women was less significant (OR = 0.95, 95% CI: 0.88–1.03). Duration of breastfeeding was associated with a non-linear reduction in breast cancer risk, with the greatest reduction observed in women who breastfed for 6 to 12 months (OR = 0.75, 95% CI: 0.64–0.87). Conclusion: This meta-analysis supports the hypothesis that breastfeeding is associated with a modest reduction in breast cancer risk, particularly for pre-menopausal women and those who breastfed for longer durations. Although the effect size is small compared to other established risk factors, breastfeeding remains an important modifiable risk factor for breast cancer prevention. Further research is needed to clarify the mechanisms underlying this association and to determine whether breastfeeding duration has a cumulative effect beyond 12 months.